Performance Evaluation of Ethiopian Bread Wheat (Triticum aestivum L.) Genotypes in Southern Ethiopia - Mengistu Meskele Alambo; Mesfin Kebede Gessese; Eyasu Wada Wachamo; Belay Yebo Melo; Zemach Sorsa Lakore; Adera Sisay Wassie; Wondimeneh Taye Haile; Fentanesh Chekole Kassie (Advances in Agriculture)
Ethiopia is not self-sufficient to meet its increasing wheat demand from domestic production partly due to a lack of improved seeds. Efforts are undertaken to fill the gap through off-season production of wheat using supplemental irrigation and modern cultivars adapted to arid areas. This study was carried out to evaluate the genetic variability and adaptability of 15 Ethiopian bread wheat genotypes at different agroecologies in Wolaita and Dawuro zones, Ethiopia. The field experiment was conducted at three locations using a randomized complete block design with three replications during the 2019/2020 main cropping season. Analysis of variance based on 11 morphological agronomic traits and two major wheat diseases revealed that there were highly significant differences (P<0.01) among the genotypes for all the traits studied at each location and combined over locations. The top three cultivars viz. Alidoro, Galema, and Honqolo exhibited higher average grain yield (GY) of 4.54 t/ha, 4.36 t/ha, and 4.0 t/ha, respectively, combined over locations. Eight of the traits (72.73%) exhibited moderate (30–60%) to high broad-sense heritability (hb2 > 60%) values. High hb2 associated with high genetic advance as percent of mean was observed for the severity of both stem and yellow rust diseases combined over locations. GY was significantly related to aboveground biomass at all locations. This study depicted that cultivar Alidoro had wider adaptability for grain yield and resistance to wheat rusts.